Determinants Failure of Exclusive Breast Feeding on Health in the City Bengkulu (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
The first 1,000 days of life program is a program to improve the quality of children in the future which one of these programs is the provision of exclusive breastfeeding. The decline in infant mortality rates slowed between 2003 to 2012 from 35 to 32 per 1,000 live births, all babies need access to key interventions such as exclusive breastfeeding. The success of these programs are driven by health workers, but the researches that analyze information about exclusive breastfeeding program on health workers, especially in Bengkulu had never been examined. The research design used mixed methods (quantitative and qualitative) on health workers in Bengkulu in 2015 who have infants aged 6-24 months (66 people), which were determined by purposive sampling. The results showed that 69.7% of the mothers did not practice exclusive breastfeeding and 54.5% did not practice early initiation of breastfeeding. Analysis of early initiation of breastfeeding factor as the dominant factor for failure of exclusive breastfeeding. The qualitative analysis showed confidence and perception of little milk production are factor for unsuccessful early initiation of breastfeeding .